Engineered Passive Glucose Uptake in Pseudomonas taiwanensis VLB120 Increases Resource Efficiency for Bioproduction - Tobias Schwanemann; Nicolas Krink; Pablo I. Nikel; Benedikt Wynands; Nick Wierckx (Microbial Biotechnology)
ABSTRACT Glucose is the most abundant monosaccharide and a principal substrate in biotechnological production processes. In Pseudomonas, this sugar is either imported directly into the cytosol or first oxidised to gluconate in the periplasm. While gluconate is taken up via a proton‐driven symporter, the import of glucose is mediated by an ABC‐type transporter, and hence both require energy. In this study, we heterologously expressed the energy‐independent glucose facilitator protein (Glf) from Zymomonas mobilis to replace the native energy‐demanding glucose transport systems, thereby increasing the metabolic energy efficiency. The implementation of passive glucose uptake in engineered production strains significantly increased product titres and yields of the two different aromatic products, cinnamic acid (+10%–15%) and resveratrol (+26%; 18.1 mg/g) in batch cultures.